ANALISIS MAKNA PADA PUISI “KAMUS KECIL” KARYA JOKO PINORBO MENGGUNAKAN PENDEKATAN SEMIOTIKA - Dede Siti Fatimah; Siti Halimah Sadiah; Restu Bias Primandhika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The "Kamus Kecil" poem by Joko Pinurbo has a unique and simple language structure. The unusual process of creation makes the reader interested. It is related to the unique and simple language used to be unique to become research material. The purpose of this study was to analyze the meaning in a poem by Joko Pinurbo or who was familiar with Jokpin entitled "Kamus Kecil". The method used in the research on Joko Pinurbo's poem "Kamus Kecil" uses qualitative research methods that examine the "content" of the object under study. In addition, this poem was dissected using a semiotic approach which converged on the assure theory about the development of linguistics. In the poem "Kamus Kecil" Jokpin stated that inspiration did not need to be sought. He is in everyday life. In other words, Jokpin wants to state that so easy poetry is created only by simple and meaningful wordplay. So that in the poem "Kamus Kecil" one of the most unique poems that researchers read. The results of the study of the poem "Kamus Kecil" are divided into three aspects; symbols, icons, indices. Among the symbols contained in the poem are signs that are generated by simple diction making the meaning contained in the poem have a unique allure. The simple and intriguing play of words raised from daily activities is a characteristic of Jokpin's poetry.